Man in Background (Czech Journal of International Relations, 1997)
The decision on the accession of the Czech Republic to the European Union rightly caused an increased interest of our public in the entire integration process, which until now was mostly considered a problem of only Western Europe and affecting us only marginally. It is undoubtedly related to the general lack of knowledge and information about what the European integration process is.Most people know that it is about economic cooperation leading to integration, but few people realize how big a role politics plays here, how much attention needs to be paid to social, cultural and other issues. If we want to fully know and understand the European integration process, we have to admit that it already has its own history, which, thanks to Europe's divided past, we hardly know at all. If we ask ourselves when it all started, we must also ask which personalities were behind the birth of the integration idea, what it originally looked like, why and how it began to proceed, how further development took place, what obstacles the process ran into, etc. Answer it is not easy to answer all of the above questions and it is not at all possible to manage it in one article. Nevertheless, even a review of one book can contribute to a gradual understanding.